Accuracy of the Moyers 75% Probability Table in Predicting Dental Arch Space in Batak Ethnic Students at the University Sumatera Utara - Arifa , Silvia; Bahirrah, Siti; Yusuf , Muslim; Sofyanti, Ervina (CoinReads Media Prima, 2025)
Introduction: Accurate prediction of dental arch space is crucial for effective orthodontic treatment planning, particularly in mixed dentition analysis. The Moyers prediction table at 75% probability is widely used to estimate space requirements for unerupted canines and premolars, but its accuracy varies across populations due to ethnic differences in tooth size and arch dimensions. This study evaluates the accuracy of the Moyers 75% probability table in predicting dental arch space among Batak ethnic students at Universitas Sumatera Utara (USU). Methods: A cross-sectional study was conducted on 60 Batak ethnic USU students (30 males, 30 females, aged 18–25 years) with normal occlusion and no history of orthodontic treatment. Dental casts were obtained, and mesiodistal widths of mandibular incisors, canines, and premolars were measured using digital calipers (accuracy 0.01 mm). Actual measurements were compared with predicted values from the Moyers 75% probability table. Discrepancies were analyzed, and accuracy was assessed as the percentage of predictions within ±1 mm of actual measurements. Results: The Moyers table overestimated canine-premolar space by an average of 1.2 mm in males and 0.9 mm in females. Accuracy within ±1 mm was achieved in 65% of cases, with significant differences between predicted and actual values (p<0.05). Sexual dimorphism was observed, with larger discrepancies in males. Conclusion: The Moyers 75% probability table shows moderate accuracy in Batak ethnic students, suggesting the need for population-specific adjustments. Further studies should explore ethnic variations to enhance orthodontic prediction models.